2015
DOI: 10.1021/ac504012a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Paired Ion Contrast Analysis: A Novel Algorithm for Analyzing Postprocessed LC-MS Metabolomics Data Possessing High Experimental Noise

Abstract: One of the consequences in analyzing biological data from noisy sources, such as human subjects, is the sheer variability of experimentally irrelevant factors that cannot be controlled for. This holds true especially in metabolomics, the global study of small molecules in a particular system. While metabolomics can offer deep quantitative insight into the metabolome via easy-to-acquire biofluid samples such as urine and blood, the aforementioned confounding factors can easily overwhelm attempts to extract rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Liang et al investigated basal metabolomic differences in control populations to putatively identify steroid metabolites as the primary discriminatory molecules (Liang et al, 2015), and therefore caution should be taken when utilizing such metabolites as radiation specific. Given the heterogeneity in the available human radiation cohorts due not only to genetic differences but also to underlying disease, it has been proposed that perhaps pairs of ions instead of single biomarkers and patterns of similar or dissimilar regulation may provide more power in distinguishing exposed from non-exposed individuals (Mak et al, 2015a). This study also further identified perturbations in lysine biosynthesis/degradation and folate biosynthesis.…”
Section: Humansmentioning
confidence: 99%
“…Liang et al investigated basal metabolomic differences in control populations to putatively identify steroid metabolites as the primary discriminatory molecules (Liang et al, 2015), and therefore caution should be taken when utilizing such metabolites as radiation specific. Given the heterogeneity in the available human radiation cohorts due not only to genetic differences but also to underlying disease, it has been proposed that perhaps pairs of ions instead of single biomarkers and patterns of similar or dissimilar regulation may provide more power in distinguishing exposed from non-exposed individuals (Mak et al, 2015a). This study also further identified perturbations in lysine biosynthesis/degradation and folate biosynthesis.…”
Section: Humansmentioning
confidence: 99%
“…Moreover, unlike transcriptomics, correlation among metabolites identified from metabolomics data may not indicate a common biological function27. Apart from the above differences, there are significant similarities between two OMICs data: (1) right-skewed distribution23, (2) great data sparsity28, (3) substantial amount of noise2930 and (4) significantly varied sample sizes3132. Due to these similarities, it is feasible to apply some of the normalization methods used in transcriptomics data analysis to the metabolomics one.…”
mentioning
confidence: 99%
“…Continued methods development will be based on more complete species and time-course response data, further refinement of sample storage and extraction methods, introducing an automated flow injection device, standardization and automation of mass-spectrometric techniques, and continued attention to new bioinformatic methods [50, 51]. The gains in sample throughput are to a large extent specific to the analytes described in this paper.…”
Section: Resultsmentioning
confidence: 99%